Long-Haul Truck Driver Training Does Not Meet Driver Needs in Canada - Malkin, Jennifer (Saf Health Work, 2021)
INTRODUCTION: Training standards for long-haul truck drivers (LHTD) are rapidly evolving in Canada, yet the opinions of the drivers themselves have not been adequately considered. The purpose was to survey LHTD on their work training history and to examine LHTD perceptions of driver training and licensing protocols. METHODS: LHTD were recruited across two Western Canadian provinces from seven different truck stops. The sample completed 207 surveys and 67 semi-structured interviews. RESULTS: The average age of the participants was 52.5 ± 11.5 years (range 24–79); 96% were men. Approximately 33% of the LHTD had at least one crash. Those who did not receive formal driver training were significantly more likely to crash than those who had received training. Participants stated that current training standards are inadequate for the industry, particularly for new drivers. According to participants, entry-level curriculums should consist of both classroom and practical training, as well as on-road observation with a senior mentor. LHTD reported that many new drivers are not equipped to drive in various contexts and settings (e.g., mountains, slippery roads). CONCLUSIONS: LHTD are not confident in the current training guidelines for novice truck drivers. Revisions to the training curriculum and standardization across Canada should be considered. PRACTICAL APPLICATION: A federal mandatory entry-level training program is needed in Canada to ensure that all new LHTD ascertain the necessary skills to drive safely. Such a program requires government involvement and input from LHTD to facilitate appropriate licensure and consistent training for all drivers.